Do the ESG scores help to select the most successful companies? - Serge Evraert; Frédérique Bardinet - Evraert (IJRDO - Journal of Business Management, 2019)
Financial performance, the main purpose for the investors, is easily measured by financial reporting. On the other hand, its numerous causes, for example the combination of the knowledge and the acts of the employees of the company, remain anonymous and are not reported. This article uses the ESG scores measured by financial analysts and portfolio managers of a French SRI fund to assess the respective influences of environmental, social, governance activities in order to select the most successful companies. For that, these scores are combined with a set of financial indicators of 143 European listed companies, collected from the database of the SRI Fund. The Companies are followed over a period of 5 years. Governance scores are significant but not those related to the environment and social activities. In order to explain the discriminant power of governance, its scores are broken down into sub-scores. The tests are significant for financial communication: the reliability of published information, the transparency, quality and stability of the management team as well as for organizational characteristics such as the separation of tasks and the quality of internal control. The results confirm the classification of companies in the two chosen categories which differ in their level of financial performance. The results suggest that governance activities are highly valued by financial analysts. This should encourage business leaders and their teams to put in place an effective governance policy. The argument is equally strong for practitioners, especially portfolio managers, who should not underestimate governance issues in their search of the most successful companies.